2012 IEEE Globecom Workshops 2012
DOI: 10.1109/glocomw.2012.6477823
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a wireless mesh network of ultra light MAVs with dynamic routing

Abstract: Abstract-This paper describes the implementation and characterisation of a mobile ad-hoc network (MANET) of ultra-light intelligent flying robots. The flying nature of the network makes it suitable to collect or disseminate content in urban areas or challenging terrain, where line-of-sight connection between the Micro Air Vehicles (MAVs) allows for more efficient communication. Dynamic routing in the network enables the nodes to intelligently establish multi-hop routes to extend the communication range or to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…(1) Network topology-based routing algorithms. The optimized link state routing (OLSR) protocol was applied to the network consisting of two micro airplanes and a ground station [12]. The results show that the OLSR cannot deal with the rapidly changing topology in a MAV network properly and quickly enough.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Network topology-based routing algorithms. The optimized link state routing (OLSR) protocol was applied to the network consisting of two micro airplanes and a ground station [12]. The results show that the OLSR cannot deal with the rapidly changing topology in a MAV network properly and quickly enough.…”
Section: Related Workmentioning
confidence: 99%
“…Else, the MAV checks whether the destination is its own neighbor node. If the destination is the neighbor, the packet is forwarded to the destination, and the algorithm ends (as shown in steps [6][7][8][9][10][11][12][13][14]. Otherwise, the MAV that is the optimal neighbor i is found by FindBestNeighbour function (step 15).…”
Section: The Dtn Est Algorithm Based On Location Estimationmentioning
confidence: 99%
“…They measured detailed data on network throughput, delay, range, and connectivity under different operating regimes and showed that the UAV has longer range and better connectivity with the ground nodes. Jimenez-Pacheco et al [22] also built a mobile ad hoc network (MANET) of light UAVs. The system has implemented a line of sight dynamic routing in the network.…”
Section: Related Workmentioning
confidence: 99%
“…According to analyzing the characteristics of the scene, messages are transmitted to the direction closer to the ground station and are allowed to be stored and carried during transmission. These methods are likely to cause some specific drones to consume a lot of energy for transmitting messages, which will constrain them from completing other tasks [11].…”
Section: Introductionmentioning
confidence: 99%